LEARNING TOOLS OF STATIC AND DYNAMIC FLUIDS: POWER POINT, VIDEO, AND EXPERIMENT MODULE - SAFITRI (NIM : 90211302); Pembimbing : Dr. Siti Nurul Khatimah, ISLAMIANI
Problem which often encountered in schools are teacher difficulties to transfer physics lessons to students. To overcome these problems, it was designed the static and dynamic fluid learning tools such as power point, video, and experiment module in this final project. Experiments to determine density of liquid, contact angle, and capillarity in static fluids were performed by using U-tube and other tube, whereas to determine the velocity of dynamic fluid is done using a plastic beaker having a hole in its side. Using hydrometer, density of oil SAE 40, coconut oil, water, and glycerine are 880 kg/m3, 910 kg/m3, 1000 kg/m3, and 1260 kg/m3. The water contact angle is 68.9o up to 69.9o, while the increase in capillarity tube is 0.00425 m for tube diameter of 0.0025 m and 0.00555 m for tube diameter of 0,002 m. By calculating flow rate from the volume graph as a function of time, the speed of liquid leaving the hole at the side of a beaker decreased with time. The percent difference between the experiment and the TorricelliÃ‚Â’s law is 20,1% - 28,5%.